1998
DOI: 10.1111/j.1399-0039.1998.tb02947.x
|View full text |Cite
|
Sign up to set email alerts
|

CTLA4 codon 17 dimorphism in patients with rheumatoid arthritis

Abstract: The genetic susceptibility to rheumatoid arthritis is conferred by genes in the human leukocyte antigen (HLA) region on chromosome 6, but additional genes may be involved to determine disease susceptibility. We have studied the distribution of the CTLA4 exon 1 polymorphism (49 A/G) in rheumatoid arthritis. This dimorphism at codon 17 results in an amino acid exchange (Thr/Ala) in the leader peptide of the expressed protein and was analyzed by PCR, SSCP and RFLP in 258 Caucasian rheumatoid arthritis patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 39 publications
3
68
1
2
Order By: Relevance
“…Initial comparison showed an increased frequency of the +49 A/G*A allele in the RA group (data not shown). As the majority of studies reporting disease association with this SNP hint towards increased frequency of the G allele (Cai et al, 2005;Lee et al, 2003;Vaidya et al, 2002;Yanagawa et al, 2000;Matsushita et al, 1999;Gonzalez-Escribano et al, 1999;Seidl et al, 1998), we wondered whether the association seen in our study could be due to any idiosyncratic characteristics specific to this control population (168 healthy blood donors). Therefore, + 49 A/G distribution in a second, distinctive Northern Irish control population consisting of 307 Northern Irish 12 to 15-year-old school children was compared to that in Group 1.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Initial comparison showed an increased frequency of the +49 A/G*A allele in the RA group (data not shown). As the majority of studies reporting disease association with this SNP hint towards increased frequency of the G allele (Cai et al, 2005;Lee et al, 2003;Vaidya et al, 2002;Yanagawa et al, 2000;Matsushita et al, 1999;Gonzalez-Escribano et al, 1999;Seidl et al, 1998), we wondered whether the association seen in our study could be due to any idiosyncratic characteristics specific to this control population (168 healthy blood donors). Therefore, + 49 A/G distribution in a second, distinctive Northern Irish control population consisting of 307 Northern Irish 12 to 15-year-old school children was compared to that in Group 1.…”
Section: Resultsmentioning
confidence: 87%
“…The authors of the latter study also found the G allele of this SNP to be associated with lower mRNA levels of soluble CTLA-4 isoform, thus providing a rationale for a functional role in susceptibility to autoimmune diseases. Table 1 summarizes all the studies that have been done to date investigating the effects of CTLA-4 gene in RA (Cai et al, 2005;Lee et al, 2003;Rodríguez et al, 2002;Vaidya et al, 2002;Hadj Kacem et al, 2001;Yanagawa et al, 2000;Matsushita et al, 1999;Gonzalez-Escribano et al, 1999;Seidl et al, 1998;Orozco et al, 2004;Lee et al, 2002;Barton et al, 2000;Milicic et al, 2001). Results have been conflicting with some studies hinting towards association with RA, while others claiming to find no association at all.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research indicates that several of the non-HLA regions linked to Type I diabetes also show linkage to other autoimmune diseases, suggesting common pathogenic pathways shared by Type I diabetes and these other disorders [127,128]. For example, the IDDM3 region on chromosome 15q26 has been reported to be linked to coeliac disease [129,130], the IDDM6 region on chromosome 18q21 has been reported to be linked to Graves disease [131] as well as multiple sclerosis and rheumatoid arthritis [69], the IDDM8 region on chromosome 6q27 has been reported to be linked to rheumatoid arthritis [132], the IDDM12 (CTLA4) region on chromosome 2q33 has been reported to be linked to coeliac disease [133,134], Graves disease [78,135], multiple sclerosis [136] and rheumatoid arthritis [137,138], the IDDM16 region on chromosome 14q32 has been reported to be linked to multiple sclerosis [139], and the chromosome 1q42 region containing an unnamed diabetes locus has been reported to be linked to systemic lupus erythematosus [140,141] (for additional examples, see [128]). Although some of these co-localizations could be coincidental, the possibility remains that at least a few IDDM loci would be more accurately called autoimmunity susceptibility loci.…”
Section: Is Positional Candidate Mapping Feasible?mentioning
confidence: 99%
“…An A-to-G substitution at nucleotide þ49 in exon 1 results in an amino acid substitution (threonine to alanine) in the leader peptide of the protein. 25 The Ala allele has been shown to predispose the individual to the development of various immune diseases, including Graves' disease, 21 Hashimoto's thyroiditis, 26 Addison's disease, rheumatoid arthritis, 27 and celiac disease. 28 In a functional study, subjects of the CTLA-4 þ49 G/G genotype were found to have reduced CTLA-4 cell surface expression upon T cell activation.…”
Section: Ctla-4 Gene Polymorphisms In Childhood Asthmamentioning
confidence: 99%